The invention of an investment incentive for pharmaceutical invention - Basheer, S; Pila, J (2011)
Pharmaceutical drugs are often hailed as the poster child for the proposition that patents foster accelerated rates of innovation. This sentiment stems, in large part, from the significantly high research and development (R&D;) costs endemic to the pharmaceutical sector. I argue that if the role of the patent regime is one of fostering higher amounts of investment in the R&D; process, it is better served by a direct investment protection regime, where the protection does not depend upon whether or not the underlying idea behind the drug is “new” and “inventive”, the two central tenets of patent law. Rather, any drug that successfully makes it past the regulatory filter ought to be entitled to protection, since its discovery and development entail significant investment and risk. Owing to the inadequacy of the current patent regime in appropriately protecting intensive pharmaceutical R&D; investments from free-riders, I propose a comprehensive investment protection regime that protects all the investment costs incurred during the drug discovery and development process. Though similar to existing data protection regimes in some respects, it differs in others. Firstly, it enables a recovery of all R&D; costs, and not only costs associated with clinical trials. Secondly, unlike patents and data exclusivity which offer uniform periods of protection, it rewards investments in a proportionate manner, wherein drug originators are entitled to protection against free-riders only until such time as they recoup their specific investments and earn a rate of return on investment that is dependent on the health value of the drug. Given that a pure market exclusivity based investment protection regime is likely to foster excessive pricing and subject the market to the dictates of a single firm, I advocate a compensatory liability model based on a novel cost sharing methodology, where follow-on entrants are free to manufacture the drug, but must pay a reasonable amount of compensation to the originator.